Catalyzing hydrogen production: Exploring plasmonic effects in self-assembled CuO/Cu2O thin films via pulsed laser deposition - Ranjan A.K.; Jha P.K.; Jha P.A.; Singh P. (My University, 2025)
Plasmonic catalysis triggers the dissociation of H 2 or adsorbed O 2 (sluggish processes) under continuous wave excitation via plasmon decay. This is coupled to interband or intraband excitation of d-band or sp-band, respectively, to levels above fermi level of metals. Here, we have studied the plasmonic and photocatalytic behavior in an environment friendly medium with AM 1.5 G sunlight of CuO/ Cu 2 O thin films fabricated by pulsed laser deposition technique in vacuum with varying thickness. We have achieved ∼ 0.59 kmol h − 1 g − 1 H 2 production in the CuO/ Cu 2 O film with a thickness of ∼ 27 nm. The role of plasmons with metal-dielectric and semiconductor-semiconductor interfaces is conducted through both experimental and theoretical approaches. The results suggest that the impact of plasmonic catalysis/synthesis is subject to the dimension, composition, and band alignment of two interface materials. © 2024 Author(s).